1992
DOI: 10.3109/00498259209053115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various medium formulations and attachment substrata on the performance of cultured ruminant hepatocytes in biotransformation studies

Abstract: 1. A procedure for the isolation and primary culture of hepatocytes from goat and cattle is described. Hepatocyte culture performance was monitored for 51 h by measuring viability, cytochrome P-450 maintenance, dealkylation of scoparone and ethylmorphine, and glucuronidation of phenol red. 2. Culture medium composition is discussed in relation to differences between splanchnic blood composition of ruminant and monogastric animal species. Main differences are in glucose and volatile fatty acid concentrations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Cells isolated from goats have been used in both hepatocyte suspension (Aiello and Armentano, 1987a,b;Aiello et al, 1989) and monolayer culture systems (Van Klooster et al, 1992). However, in the present study, satisfactory monolayers were obtained with much lower repeatability from goat liver.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Cells isolated from goats have been used in both hepatocyte suspension (Aiello and Armentano, 1987a,b;Aiello et al, 1989) and monolayer culture systems (Van Klooster et al, 1992). However, in the present study, satisfactory monolayers were obtained with much lower repeatability from goat liver.…”
Section: Resultsmentioning
confidence: 52%
“…Several abstracts (Donkin et al, 1990(Donkin et al, , 1991(Donkin et al, , 1992Cadorniga et al, 1992) and one paper (Emmison et al, 1991) have reported the use of ruminant parenchymal cell monolayers t o study hormonal regulation of hepatic metabolism. Xenobiotic metabolism has also been investigated using ruminant hepatocyte monolayers (Shull et al, 1986;Van Klooster et al, 1992). The purpose of this report is to provide a complete description of the technique for establishing bovine hepatocyte monolayers and to characterize changes in cellular metabolism during their extended culture.…”
Section: Introductionmentioning
confidence: 99%
“…These attempts include modifying the composition of the medium (by addition of hormones, chemicals, ligands, and/or inducers to the culture medium) or by incorporating different cell types as in a co-culture model. [34][35][36][37] From their work, it appears that the life time of the primary cultures can be extended by modifying the conditions of the culture. Perhaps one of the significant findings in our study is that porcine hepatocyte culture supports the maintenance of cyp2C19 and 3A4, important human iosforms that are involved in the metabolism of many xenobiotics such as diazepam, as well as phase II glucuronidation activities without a need for induction.…”
Section: Discussionmentioning
confidence: 99%
“…Liver microsomes is one of the most commonly used in vitro systems because it is cheaper, has good reproducibility and has simple preparation by using differential centrifugation [14]. In addition, the primary hepatocytes culture model played a significant role in the research of phase I and phase II drug biotransformations [15,16], which provided the most in vivo-like responses [17]. Gastrointestinal microflora was also necessary for the metabolism in vitro owing to various toxicological sequelae by intestinal microflora [18,19].…”
Section: Cyadoxmentioning
confidence: 99%